Phase III study of bevacizumab plus docetaxel compared with placebo plus docetaxel for the first-line treatment of human epidermal growth factor receptor 2-negative metastatic breast cancer - Miles, David W.; Chan, Arlene; Dirix, Luc Y.; Cortés, Javier; Pivot, Xavier; Tomczak, Piotr; Delozier, Thierry; Sohn, Joo Hyuk; Provencher, Louise; Puglisi, Fabio; Harbeck, Nadia; Steger, Guenther G.; et al. (Journal of clinical oncology, 2010)
PURPOSE: The efficacy and safety of combining bevacizumab (7.5 and 15 mg/kg) with docetaxel as first-line therapy for human epidermal growth factor receptor 2 (HER2) -negative, locally recurrent or metastatic breast cancer (MBC) was investigated in a three-arm, placebo-controlled, phase III trial. - PATIENTS AND METHODS: Patients (N = 736) were randomly assigned to docetaxel 100 mg/m(2) plus either placebo or bevacizumab 7.5 or 15 mg/kg every 3 weeks. The primary end point was progression-free survival (PFS); secondary end points included best overall response, duration of response, time to treatment failure, overall survival, and safety. - RESULTS: Combination of bevacizumab 15 mg/kg, but not 7.5 mg/kg, with docetaxel showed superior median PFS (mPFS) to placebo plus docetaxel in unstratified analysis (placebo mPFS, 8.2 months; 7.5 mg/kg mPFS, 9.0 months [hazard ratio (HR), 0.86; P = .12]; 15 mg/kg mPFS, 10.1 months [HR, 0.77; P = .006]) and stratified analysis (placebo mPFS, 8.1 months; 7.5 mg/kg mPFS, 9.0 months [HR, 0.80; P = .045]; 15 mg/kg mPFS, 10.0 months [HR, 0.67; P < .001]). Response rates in patients with measurable disease at baseline also increased with bevacizumab 15 mg/kg (46% [placebo] v 55% [7.5 mg/kg; P = .07] and 64% [15 mg/kg; P < .001]). Combination with bevacizumab had limited impact on the known toxicity profile of docetaxel. - CONCLUSION: Combination of bevacizumab with docetaxel did not significantly impact on the safety profile of docetaxel. Bevacizumab 15 mg/kg every 3 weeks significantly increased PFS when combined with docetaxel as first-line therapy for MBC compared with docetaxel plus placebo.
Gesehen am 26.04.2023